Entwicklungstendenzen der betriebswirtschaftlichen Ausbildung an einer öffentlichen Hochschule - Hans-Ulrich Küpper (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2006)
– Due to the rising relevance of the economy and economic questions in the 20th century, Business Administration has become an important subject in higher education. Its fast growing student numbers during the last decades show its weight within the higher education institutions, even though it is a quite young direction of study. This article works out the main determinants as well as the structural changes in Business Administration in tertiary education. As a result of the transition to bachelor and master programs of study and the reform of the higher education sector in Germany the education in Business Administration currently undergoes deep changes. The status quo of these reforms as well as its inherent chances and risks are analysed in this article as well.;Die Betriebswirtschaftslehre ist ein relativ junges Fach. Mit der zunehmenden Bedeutung der Wirtschaft im 20. Jahrhundert sind seine Studentenzahlen und sein Gewicht innerhalb der Hochschulen gewachsen. Der Betrag arbeitet die wichtigsten Bestimmungsgrößen und strukturellen Veränderungen der BWL-Ausbildung an den Hochschulen heraus. Durch die gegenwärtige Reform der Universitäten und den Übergang auf ein Bachelor- und Master-Studium befindet sich diese in einem deutlichen Umbruch, dessen gegenwärtige Ausprägung mit den darin enthaltenen Chancen und Risiken näher untersucht werden.
urn:nbn:de:bvb:19-epub-1239-7
Keywords: A22; A23; I23; 650; business administration; higher education; university; bachelor; master; Betriebswirtschaftslehre; Hochschule; Universität; Entwicklung; Ausbildung